Faktor-Faktor Yang Memengaruhi Mahasiswa Akuntansi Dalam Memilih Karier Sebagai Akuntan Publik - Yulitasari, Isakiwit; Iqbal, Syaiful (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to obtain empirical evidence on whether Financial Rewards, Work Environment, Personality, Social Values, Professional Recognition, and Job Market Considerations are considered by accounting students in choosing a career as a public accountant. The population in this study includes accounting students from both public and private universities in Indonesia, and the samples are selected through purposive sampling methods. The results indicated that in choosing a career as a public accountant, accounting students considered two significant factors including the work environment and personality; whist, financial rewards, social values, professional recognition, and job market considerations were not taken into account.